Decarbonization of manufacturing at Volvo GTO - Serino Olander, Andreas; Albuquerque Wolf, Lucas (My University, 2022)
Volvo Group Trucks Operations is the industrial entity within Volvo Group responsible for truck manufacturing with 40 facilities under management. The organization’s operations span across the globe contributing to carbon emissions and therefore, to climate change. Climate change has and will alter our surroundings by imposing climate patterns such as extreme weather events that put pressure on the survival of humans and our economic system. In response to this, there is an increased demand for a better commitment to environmental practices, including from companies such as Volvo Group. This study aims to contribute to lowering the environmental impact of Volvo GTO by providing a feasibility assessment for the implementation of distinct solutions of decarbonization strategies. For this, a literature review of current methods and practices that aim toward carbon reduction in manufacturing was performed. In addition, several interviews with Volvo GTO employees, as well as external experts, were conducted. Based on the data collected, a decarbonization framework was elaborated containing six strategic areas that are considered key in tackling carbon emissions: Fuel shift;structural change (electrification); carbon capture; process efficiency; technological replacement; and circularity. Each strategy includes multiple solutions that are assessed regarding their feasibility potential using a SWOT analysis. The study concludes that decarbonization at the facility level is achieved through multiple strategies and solutions that must be placed in the context of the local community to help the transition toward a more sustainable society.
Keywords: Decarbonization, sustainability, automotive industry, manufacturing, renewable energy.